2016
DOI: 10.3389/fmicb.2016.00567
|View full text |Cite
|
Sign up to set email alerts
|

Sero-Prevalence and Genetic Diversity of Pandemic V. parahaemolyticus Strains Occurring at a Global Scale

Abstract: Pandemic Vibrio parahaemolyticus is an emerging public health concern as it has caused numerous gastroenteritis outbreaks worldwide. Currently, the absence of a global overview of the phenotypic and molecular characteristics of pandemic strains restricts our overall understanding of these strains, especially for environmental strains. To generate a global picture of the sero-prevalence and genetic diversity of pandemic V. parahaemolyticus, pandemic isolates from worldwide collections were selected and analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 49 publications
1
20
0
Order By: Relevance
“…This data set only marks the beginning of longitudinal studies that will help us to dissect trends pathogens’ genetic microevolution overtime. While, ST3 presented the most dominant ST in V. parahaemolyticus , consistent with previous study in Asian countries ( Han et al, 2016 ), it strikingly differs from the predominant types in Maryland, United: ST631 and ST36 ( Haendiges et al, 2015 ) not found in our study. This is not surprising since the origins of V. parahaemolyticus at both sites are linked to Pacific and Atlantic Ocean, respectively, and involve different continents.…”
Section: Discussionsupporting
confidence: 92%
“…This data set only marks the beginning of longitudinal studies that will help us to dissect trends pathogens’ genetic microevolution overtime. While, ST3 presented the most dominant ST in V. parahaemolyticus , consistent with previous study in Asian countries ( Han et al, 2016 ), it strikingly differs from the predominant types in Maryland, United: ST631 and ST36 ( Haendiges et al, 2015 ) not found in our study. This is not surprising since the origins of V. parahaemolyticus at both sites are linked to Pacific and Atlantic Ocean, respectively, and involve different continents.…”
Section: Discussionsupporting
confidence: 92%
“…STs were assigned to clonal complexes (CCs) using eBURST v3 (Imperial College, London, UK), as described previously (Han et al, 2016). A CC was defined conservatively as a cluster of STs with primary founders positioned centrally in an eBURST diagram in which all STs are linked as single-locus variants (SLVs, two STs differing from each other at a single locus) to at least one other ST. For each CC, eBURST identifies the ST that is most likely to represent the founding genotype (the primary founder).…”
Section: Mlst Analysis and Phylogenetic Analysismentioning
confidence: 99%
“…Therefore, the current assay presents a simple and pragmatic scheme for the rapid and accurate identification of V. parahaemolyticus serotypes, which is especially suited for real-time applications such as outbreak situations involving large number of samples be processed quickly in a short period of time. In developing this assay, we chose 11 V. parahaemolyticus serotypes that represented 90% of all serotypes isolated from human infections over a 10-year period (2007–2017) in Shenzhen, China; many of which are also commonly reported among infections domestically (Han et al, 2017) and worldwide (Velazquez-Roman et al, 2014; Han et al, 2016). Given its clinical relevance, the current assay could serve as an invaluable tool for clinical and public health laboratories.…”
Section: Discussionmentioning
confidence: 99%
“…In 1996, the emergence of a more virulent serotype O3:K6 was subsequently being recognized as a pandemic clone owing to its rapid dissemination and the cause of numerous gastroenteritis outbreaks globally (Nair et al, 2007). To date, the pandemic clone and its serovariants are known to represent 49 serotypes, which are widely distributed among 22 countries in Asia, Europe, America and Africa (Han et al, 2016). In China, up to 27 pandemic serovariants have been found amongst clinical samples, in which O3:K6, O4:K68, and O1:KUT predominated (Han et al, 2017).…”
Section: Introductionmentioning
confidence: 99%